1999
DOI: 10.1089/end.1999.13.587
|View full text |Cite
|
Sign up to set email alerts
|

Endoprosthesis Implantation in the Treatment of Recurrent Urethral Stricture: A Multicenter Study

Abstract: Permanent urethral endoprostheses can produce excellent results in patients with recurrent urethral strictures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…There has previously been some interest into the use of urethral stents, both temporary and permanent for the treatment of anterior urethral strictures. Stents were associated with significant complications including perineal discomfort (86%), painful erection (44%) and recurrence (29%) in patients with short strictures using the UroLume stent [35] . Moreover, their use can make later reconstruction technically more difficult.…”
Section: Anterior Urethral Stricturesmentioning
confidence: 99%
“…There has previously been some interest into the use of urethral stents, both temporary and permanent for the treatment of anterior urethral strictures. Stents were associated with significant complications including perineal discomfort (86%), painful erection (44%) and recurrence (29%) in patients with short strictures using the UroLume stent [35] . Moreover, their use can make later reconstruction technically more difficult.…”
Section: Anterior Urethral Stricturesmentioning
confidence: 99%
“…The use of biodegradable materials has increased over the last decade in all fields of surgery, especially in urology [1]. The development of biodegradable stents for urological use started in the late 1980s, which is promising and ready to be tested in clinical trials [2]. The stents gradually achieved their properties of self-expansion and controlled gradual degradation [3].…”
Section: Introductionmentioning
confidence: 99%
“…6 More data revealed that patients experienced early complications of perineal discomfort (86%) and dribbling (14%) as well as painful erection (44%), mucous hyperplasia (44%), incontinence (14%) and recurrence (29%). 7 The urethral patency rate continued to decrease with time, as did patient satisfaction. De Vocht et al evaluated patient satisfaction 10 years after UroLume stent placement and found that only 2 of 15 were satisfied with the stent.…”
Section: Discussionmentioning
confidence: 91%